UPPER DEVONIAN-LOWER CARBONIFEROUS CONODONTS FROM CHIANG DAO CHERTS, NORTHERN THAILAND (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
In Northern Thailand, radiolarites (radiolarian cherts) are very common and their study provides an important tool to understand the regional geology and moreover to localise the suture zone(s). Some of these deep and distal oceanic series yield conodonts which provide to obtain precise age datings. The present work is focused on the Upper Devonian and Lower Carboniferous conodonts from the Chiang Dao area (Chiang Mai province). The conodont faunas from these oceanic cherts display juvenile characters which are interpreted to be a result from a constraining environment.